Study of the Oxygen Evolution Reaction at Strontium Palladium Perovskite Electrocatalyst in Acidic Medium - Eskandrani, Areej A. (Int J Mol Sci, 2020)
The catalytic activity of Sr(2)PdO(3), prepared through the sol-gel citrate-combustion method for the oxygen evolution reaction (OER) in a 0.1 M HClO(4) solution, was investigated. The electrocatalytic activity of Sr(2)PdO(3) toward OER was assessed via the anodic potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The glassy carbon modified Sr(2)PdO(3) (GC/Sr(2)PdO(3)) electrode exhibited a higher electrocatalytic activity, by about 50 times, in comparison to the unmodified electrode. The order of the reaction was close to unity, which indicates that the adsorption of the hydroxyl groups is a fast step. The calculated activation energy was 21.6 kJ.mol(−1), which can be considered a low value in evaluation with those of the reported OER electrocatalysts. The Sr(2)PdO(3) perovskite portrayed a high catalyst stability without any probability of catalyst poisoning. These results encourage the use of Sr(2)PdO(3) as a candidate electrocatalyst for water splitting reactions.